2021
DOI: 10.1016/j.ijchp.2020.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Active school travel is associated with fewer suicide attempts among adolescents from low-and middle-income countries

Abstract: Background/Objective: This study explored the association between active school travel (AST) and suicide attempts among adolescents in low- and middle-income countries (LMICs). Method: We used the data from the Global School-based Health Survey, including 127,097 adolescents aged 13-17 years from 34 LMICs. A self-reported survey was used to collect data on AST and suicide attempts as well as some variables. Multivariable logistic regression was performed to assess the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Participants having 5 days or more for walking or cycling were regarded as being active, whereas those not reporting 5 days or more for walking or cycling were regarded as being passive. The rational for selecting 5 days or more is that adolescents normally have 5 days for schooling per week, which is in line with a previous study [27].…”
Section: Active School Travel (Exposure)supporting
confidence: 82%
“…Participants having 5 days or more for walking or cycling were regarded as being active, whereas those not reporting 5 days or more for walking or cycling were regarded as being passive. The rational for selecting 5 days or more is that adolescents normally have 5 days for schooling per week, which is in line with a previous study [27].…”
Section: Active School Travel (Exposure)supporting
confidence: 82%
“…To investigate the potential factors that influence suicide-related behaviors, most previous studies have examined only a few lifestyle behaviors (e.g., physical activity, sleep) ( 8 , 18 ), and have not yet examined others. As such, previous research may offer limited results.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analytical review ( 5 , 6 ) indicated an association between higher PA levels and lower suicidal ideation ( 7 ). Even low levels of PA was found to be associated with a lower risk for suicidal ideation ( 8 ). In contrast, sedentary adolescents have been found to have a greater risk for indulging in suicide-related behaviors ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the associations established in the extant literature ( 38 , 39 , 46 , 47 ) and, more importantly, their availability in the GSHS dataset, the following variables were included as covariates; sex, age, physical fighting, current cigarette use, loneliness, number of close friends, peer support, parental connectedness, and parental bonding were considered as control variables. Specifically, to facilitate the age-stratified analysis, we classified participants into two categories: younger adolescents (aged 12–14 years) and older adolescents (aged 15–17 years) based on the common age groups used to distinguish adolescence stages ( 48 ).…”
Section: Methodsmentioning
confidence: 99%